HOTEL COMPANIES AT BUCHAREST STOCK EXCHANGE. WHAT DO THEY OFFER TO INVESTORS? - POP, Cornelia (Studia Universitatis Babeș-Bolyai Negotia, 2023)
Hotel groups listed on various security exchanges have the tendency to be representative for their respective country and/or to be emblematic worldwide. They expand and evolved from an owner-operator business model, still dominant in the 1980s, toward a sophisticated combination of the owner-operator model and asset-light business model. In the case of Romania, the owner-operator business model is dominant and is the common ground for the hotel companies listed at Bucharest Stock Exchange. The present paper has the following objectives: a) to investigate which of the former hotel companies listed on Rasdaq were chosen to be transferred on the new alternative trading system; b) if new hotel companies were willing to become publicly traded on BVB or in AeRO; c) to identify the portfolio of hotels for the listed companies, and d) to investigated the trading frequency, volume and value, and extract potential patterns. The period under scrutiny is May 2015 – May 2023. Based on the findings of the present paper the Romanian listed hotel companies do not attract the investors’ attention since they do not offer too much. Some of the problems might be generated by the low free-float and controlling shareholders/groups. Though, the main problems seem to be related to the companies’ lack of proper transparency regarding their activities (and profit centers), hotel/lodging portfolios, and the absence of (at least) domestic known brand. JEL Classification: Z31, Z33, G10 Article history: Received: June 9, 2023; Reviewed: July 14, 2023; Accepted: July 28, 2023; Available online: July 31, 2023; Available print: August 30, 2023.